Dielectric switching, SHG response and Pd(ii) adsorption of a multifunctional phase-transition complex. Issue 22 (6th October 2021) - Wang, Yu-Zhen; Shi, Ping-Ping; Xu, Ke; He, Lei; Meng, Xin; Ye, Qiong
Abstract : One-dimensional coordination polymer [(C2 H4 OH)C4 H9 NS]CdCl3 has the performance of dielectric switching and SHG response. And the compound can adsorb precious Pd(ii ) and the adsorption could be monitored by dielectric anomaly and SHG signal. Abstract : A one-dimensional coordination polymer [(C2 H4 OH)C4 H9 NS]CdCl3 (1 ) with flexible N -(2-hydroxyethyl)thiomorpholinium cations coordinating to central metal Cd crystallized in a chiral space group P 21 21 21 and showed a reversible phase transition at 174.4/162.8 K, which corresponded to the second harmonic generation (SHG) activity and dielectric switching. The introduction of a thioether group enables 1 to adsorb Pd(ii ) metal ions and the SHG signal and dielectric switching disappeared after adsorption; hence, Pd(ii ) adsorption can be monitored by the measurements of SHG and dielectric switching. This study emphasizes the advantages of introducing functional groups into the phase transition materials and presents a new approach to design multifunctional materials.